Early results from a prospective, single-arm European trial on decellularized allografts for aortic valve replacement: the ARISE study and ARISE Registry data. (9th May 2020) - Horke, Alexander; Tudorache, Igor; Laufer, Günther; Andreas, Martin; Pomar, Jose L; Pereda, Daniel; Quintana, Eduard; Sitges, Marta; Meyns, Bart; Rega, Filip; Hazekamp, Mark; Hübler, Michael; et al.
Abstract: OBJECTIVES: Decellularized aortic homografts (DAH) may provide an additional aortic valve replacement option for young patients due to their potential to overcome the high early failure rate of conventional allogenic and xenogenic aortic valve prostheses. METHODS: A prospective, European Union-funded, single-arm, multicentre, safety study was conducted in 8 centres evaluating non-cryopreserved DAH for aortic valve replacement. RESULTS: One hundred and forty-four patients (99 male) were prospectively enrolled between October 2015 and October 2018, mean age 33.6 ± 20.8 years; 45% had undergone previous cardiac operations. Mean implanted DAH diameter 22.6 ± 2.4 mm and mean durations for the operation, cardiopulmonary bypass and cross-clamp were 341 ± 140, 174 ± 80 and 126 ± 43 min, respectively. There were 2 early deaths (1 LCA thrombus on day 3 and 1 ventricular arrhythmia 5 h postop) and 1 late death due to endocarditis 4 months postoperatively, resulting in a total mortality of 2.08%. One pacemaker implantation was necessary and 1 DAH was successfully repaired after 6 weeks for early regurgitation following subcoronary implantation. All other DAH were implanted as a free-standing root. After a mean follow-up of 1.54 ± 0.81 years, the primary efficacy end points peak gradient (mean 11.8 ± 7.5 mmHg) and regurgitation (mean 0.42 ± 0.49, grade 0–3) were excellent. At 2.5 years, freedom from explantation/endocarditis/bleeding/stroke was 98.4 ± 1.1%/99.4 ± 0.6%/99.1 ± 0.9%/99.2 ± 0.8%, respectively, with results almost identical to those in an age-matched Ross operation cohort of 212 patients (mean age 34 years) despite DAH patients having undergone >2× more previous procedures. CONCLUSIONS: The initial results of the prospective multicentre ARISE trial show DAH to be safe for aortic valve replacement with excellent haemodynamics in the short follow-up period.